Widespread Natural Occurrence of High Titers of Neutralizing Antibodies to a Specific Class of Endogenous Mouse Type-C Virus - Aaronson, Stuart A. (1974)
Mouse cells contain several biologically distinguishable endogenous type-C viruses. In the present studies, the immunologic response of different strains of mice to the natural expression of these viruses has been examined. High titers of neutralizing antibodies have been detected to a class of virus that lacks the ability to exogenously infect mouse cells. The expression of this virus, in vivo as well as in vitro, is shown to be vertically transmitted as a dominant genetic trait. The findings indicate the widespread occurrence of this endogenous virus and the ability of the mouse to immunologically respond to a class of type-C virus whose mode of transmission is similar to that of cellular genes.